PENELUSURAN BAKAT MINAT PADA SISWA SMA DI BEKASI - Marsidi, Sitti Rahmah; Hatta, Andi Rina (Jurnal Pengabdian Masyarakat AbdiMas, 2019)
AbstractPreliminary assessment data obtained from community service partners (abdimas), namely students are often confused in choosing lecture majors when there are majors for college invitation students, the percentage is quite high for students who continue their education to college, and schools do not yet have a specific method the results are valid, objective, and reliable. Therefore, special, valid, objective, and objective methods are needed to answer the problems faced by partners and students. One method that can be done based on these problems is a psychological assessment in the form of a test of aptitude and interest. This test aims to explore the talents and interests of students towards a field of work that will later be connected with the department / faculty at a college or university. Talent or aptitude is an innate ability or potential that still needs to be trained and developed so that it can be realized. While interest is a relatively sedentary trait in someone who has an influence on learning. The results of this psychological assessment are in the form of information about intelligence, talents and interests, personalities, and majors in universities, especially the University of Esa Unggul. The community service activities were attended by 208 students from Taman Harapan 1 High School and Cindera Mata High School Bekasi City and on 19, 20 and July 21 2018. Out of 208 data, only 156 data can be processed / interpreted and 52 data cannot be processed. The interest of the work most interested in participants is scientific, then medical, and clerical. The most recommended department or faculty at University of Esa Unggul is for participants who are tailored to their interest in the Faculty of Health, followed by the Faculty of Economics and Business and the Faculty of Design and Creative Industries. A total of 21 participants who did not have faculty recommendations at University of Esa Unggul. It is expected that from this talent and interest tracking program can support students when determining their career fields that are suitable for their talents and interests, and can increase enthusiasm, motivation, and achievement in students in the future. Keywords: aptitude test, interest test, high school student AbstrakData preliminary assessment yang didapatkan pada mitra pengabdian kepada masyarakat (abdimas) yaitu siswa seringkali bingung memilih jurusan perkuliahan ketika ada pemilihan jurusan untuk siswa jalur undangan perguruan tinggi, prosentasi cukup tinggi pada siswa yang melanjutkan pendidikan ke perguruan tinggi, dan sekolah belum memiliki metode khusus yang hasilnya valid, objektif, dan reliabel untuk menggambarkan bakat minat dan jurusan di perguruan tinggi untuk siswanya. Oleh karena itu, dibutuhkan metode khusus yang valid, objektif, dan reliabel dalam menjawab permasalahan yang dihadapi mitra dan siswa. Salah satu metode yang dapat dilakukan berdasarkan permasalahan tersebut adalah asesmen psikologi berupa tes bakat minat yang bertujuan menelusuri bakat dan minat siswa terhadap suatu bidang pekerjaan yang nantinya akan dikaitkan dengan jurusan/fakultas di perguruan tinggi. Bakat merupakan kemampuan bawaan atau potensi yang masih perlu dilatih dan dikembangkan agar dapat terwujud. Sementara minat merupakan suatu sifat yang relatif menetap pada diri seseorang yang memiliki pengaruh besar terhadap belajar. Hasil dari asesmen psikologi ini berupa informasi mengenai inteligensi, bakat dan minat, kepribadian, serta jurusan di Perguruan Tinggi, khususnya Perguruan Tinggi Universitas Esa Unggul. Abdimas ini diikuti oleh 208 siswa dari SMA Taman Harapan 1 dan SMA Cindera Mata Kota Bekasi serta dilaksanakan pada 19, 20, dan 21 Juli 2018. Dari 208 data, hanya 156 data yang dapat diolah/interpretasi dan 52 data tidak dapat diolah. Minat pekerjaan paling banyak diminati partisipan adalah scientific, kemudian medical, dan clerical. Jurusan atau fakultas di Universitas Esa Unggul yang paling banyak direkomendasikan yaitu Fakultas Ilmu Kesehatan, disusul kemudian Fakultas Ekonomi dan Bisnis serta Fakultas Desain dan Industri Kreatif. Sebanyak 21 partisipan tidak memiliki rekomendasi fakultas di Universitas Esa Unggul. Diharapkan dari program penelusuran bakat minat ini dapat mendukung siswa ketika menentukan bidang karirnya kelak yang sesuai dengan bakat dan minatnya, serta dapat meningkatkan semangat, motivasi, dan prestasi pada siswa di perguruan tinggi kelak. Kata kunci : tes bakat, tes minat, siswa SMA